Diabetic ketoacidosis at the onset of Type 1 diabetes in young children Is it time to launch a tailored campaign for DKA prevention in children - Iovane, Brunella; Cangelosi, Antonina Marta; Bonaccini, Ilaria; Di Mauro, Dora; Scarabello, Chiara; Panigari, Arianna; Tiri, Alessandra; Mastrorilli, Carla; Fainardi, Valentina; Dodi, Icilio; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2018)
Aim: To analyze clinical characteristics associated with the occurrence of diabetic ketoacidosis (DKA) at the onset of type 1 diabetes (T1D) in children aged <5 years in order to identify early signs or symptoms useful to prevent DKA appearance. Methods: Data of patients with newly diagnosed TID aged <5 years (Group 1) and 6-10 years old (Group 2) coming from the province of Parma were collected in the period 2012-2016. Results: Mild/moderate ketoacidosis at diabetes diagnosis occurred more frequently in Group 1 than in Group 2 patients (p<0.0015). Severe DKA incidence was higher in children below 5 (21.8%) than in those over 5 years of age (3.75%; p=0.021). Latent period before overt T1D diagnosis was longer in Group 1 than in Group 2 patients (p=0.0081). During this latent period similar indicators were recorded among parents of children <3 years old: frequent use of disposable baby diapers (87%), wet baby diapers because of a large amount of urine (86%), body weight loss (79%). In children aged 3-4 years reported symptoms consisted of polyuria (89%), polydipsia (79%), fatigue (72%). In Group 2 patients predominant signs concern unusual episodes of enuresis. Conclusions: We believe that it is time to launch a DKA prevention campaign tailored for children under 5 years old and focused just on the above-mentioned three warning signs. Information program must involves pediatricians, pediatric nurses, new moms and nursery school teachers.